KUAT TEKAN SANDWICH PANEL EXPANDED POLYSTYRENE PENAMBAHAN PLESTERAN DAN KAWAT LOKET - Sustika Pratiwi; Ashar Saputra; Ali Awaludin (TEKNISIA, 2020)
Housing needs are increase up to one million units per year. Indonesia is also one of the countries that is often affected by earthquake so that the people and Indonesian government need to work on making simple, fast and safe houses. One way is use lightweight panel walls. To increase the strength of the panel wall, reinforcement is needed. This study aims to determine the effect of adding plaster and wiremesh to the compressive strength of expanded polystyrene (EPS) sandwich panel walls. This study uses precast specimen expanded polystyrene panel walls size 180 cm × 61 cm. Consists of panel walls without reinforcement, panel walls with plaster and wiremesh space of 1 cm and 2 cm. The results of the average vertical compressive strength of the EPS panel wall obtained at 0,62 MPa, the panel with the addition of plaster and wiremesh with 1 cm space of 0,77 MPa and the highest compressive strength obtained from panel with the addition of plaster and wiremesh with 2 cm space of 0,84 MPa. The results showed that the addition of plaster and wiremesh will increase the compressive strength of expanded polystyrene sandwich panel walls.